Bacterial cellulose/cashew gum films as probiotic carriers - Oliveira-Alcântara, Ana Vitória (2020)
This study was carried out to obtain probiotic films with good stability by combining spore-forming, resistant bacteria (Bacillus coagulans) with a biopolymer mix (bacterial cellulose BC and cashew gum - CG) as a carrier matrix. Fructooligosaccharides (FOS) were used as prebiotic. Four different films were produced, namely, Co (control), Pro (added with probiotic), Pre (containing the prebiotic FOS), and Syn (synbiotic films containing probiotic and FOS). Although the tensile and barrier properties of films have been undermined by probiotic and FOS, those properties have remained within the values needed for food applications. Most films (except Pre) exhibited hydrophobic character (contact angles > 90°). FOS enhanced probiotic viability upon processing. The storage stability of probiotics was very good; even at 37 °C, the viability loss did not surpass 1 log cycle, due to the resistance of B. coagulans and the protective role of BC. Moreover, no cytotoxic effect of the films was observed on Caco-2 cells.